Revealing the origin of the vertical hysteresis loop shifts in an exchange biased Co/YMnO 3 bilayer - Barzola Quiquia, J. (2012)
We have investigated exchange bias effects in bilayers composed of the antiferromagnetico-YMnO3 and ferromagnetic Co thin film by means of SQUID magnetometry,magnetoresistance, anisotropic magnetoresistance and the planar Hall effect. Themagnetization and magneto-transport properties show pronounced asymmetries in the fieldand magnetization axes of the field hysteresis loops. Both exchange bias parameters, theexchange bias field HE.T/ as well as the magnetization shift ME.T/, vanish around the Neeltemperature TN = 45 K. We show that the magnetization shift ME.T/ is also measured by ashift in the anisotropic magnetoresistance and planar Hall resistance having a similartemperature dependence as the one obtained from magnetization measurements. Because theo-YMnO3 film is highly insulating, our results demonstrate that the ME.T/ shift originates atthe interface within the ferromagnetic Co layer. To show that the main results obtained aregeneral and not because of some special characteristics of the o-YMO3 layer, similarmeasurements were done in Co/CoO micro-wires. The transport and magnetizationcharacterization of the micro-wires supports the main conclusion that these effects are relatedto the response of the ferromagnetic Co layer at the interface.